Antisemitism, Anti-Judaism, and Biblical Interpretation - Setzer, Claudia 1952- (2025)
Antisemitism, the hatred of Jews as a people, and anti-Judaism, the criticism and misrepresentation of the religion of the Jews, persist in literature and biblical studies today. Even progressive thinkers who otherwise champion human rights, including women’s equality, abolition of slavery, and contemporary reform, sometimes slip into antisemitic and anti-Jewish tropes by relying on two types of thinking, dualism and scapegoating, which distance one’s own group by defining another as “not us,” in an effort to make Christianity look better by making Judaism look worse. Such an approach allows one to jettison objectionable parts of one’s own tradition, rather than take responsibility for them, while undermining interfaith relations.
Keywords: Woman’s Bible; Jewish and Christian Self-Definition; Jewish-Christian relations; Paul the Apostle and Women; Jesus and Women; Scapegoating; Dualism; Pharisees; Jews; Anti-judaism; Antisemitism